Challenges of Applying On-Site Photovoltaic System At Environmetally Friendly Buildings In Indonesia - Esterlita Hisamatsu (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
Seventh goal of the "Sustainable Development Goals (SDGs)" is clean and affordable energy to increase the proportion of renewable energy. However, power plants in Indonesia are still dominated by non renewable energy. Therefore, it is necessary to have renewable energy technologies such as photovoltaic that can be installed on-site in buildings as an alternative clean electricity supplier. Even though Indonesia has abundant sun energy, domestic photovoltaic development is relatively slow. This research aims to identify obstacles to the application of photovoltaic as an on-site electrical system in Indonesia by spreading questionnaire to experts and users. Each question in the questionnaire is related to the understanding of the three pillars of sustainability (environment, social, and economic) related to on-site photovoltaic. The results of the data will be tested using the one sample t-test method to identify the environmental barriers, social barriers, and economic barriers. The results of this study indicate that the constraints of photovoltaic as an on-site power plant are generally dominated by social and economic barriers. Meanwhile, environmental barriers are recessive.